KAJIAN STRATEGI MANAJEMEN R&D PERUSAHAAN FURNITURE - Susi Hartanto (Jurnal PATRA, 2021)
This article’s content is mainly about R&D management with case study in New Elegant, Ltd., Vietnam. Aside from furniture production and building relation with trading houses and buyers, plenty of design works, sample making, revision with 3 factory partners require good management strategies in order to keep R&D process well run. Modularity, carry over details (COD), and point of parity (POP) are useful strategies for quick daily design making. Revitalization and point of difference (POD) strategies are applied occasionally as it takes longer time to develop. Database, investment on expert human resources not owned by factories, monitoring, and intense communication are keys to R&D management in this company.